2012
DOI: 10.3109/00365513.2012.686788
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of alcoholism: an updated review

Abstract: Current status of carbohydrate defi cient transferrin,total serum sialic acid, sialic acid index of apolipoprotein J and serum b-hexosaminidase as markers for alcohol consumption. Addiction, 2003:98;(Suppl. 2), 45 -50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…When drinking resumes, even low levels of ethanol can lead to a rapid re-elevation [4]. CDT is the only test approved by the Food and Drug Administration for the identification of heavy alcohol use [15]. Low-sensitivity CDT is apparent in women, and occasional and young drinkers, as well as the general population.…”
Section: Glycoconjugate Biomarkersmentioning
confidence: 99%
“…When drinking resumes, even low levels of ethanol can lead to a rapid re-elevation [4]. CDT is the only test approved by the Food and Drug Administration for the identification of heavy alcohol use [15]. Low-sensitivity CDT is apparent in women, and occasional and young drinkers, as well as the general population.…”
Section: Glycoconjugate Biomarkersmentioning
confidence: 99%
“…The prevalence of hazardous drinking as measured by the AUDIT in different groups of workers has been mentioned by several authors in different countries 26−28) . The %CDT has been evaluated extensively as a marker of alcohol use and abuse 29,30) and has been observed to have high sensitivity and specificity in distinguishing chronic, hazardous drinking subjects from abstainers or very light social drinkers 25,31) . However, it has been less frequently used in the workplace 32) .…”
Section: Discussionmentioning
confidence: 99%
“…Such circumstances led us to not use a quantity-frequency survey for detecting hazardous drinking but instead to use the total AUDIT (Alcohol Use Disorders Identification Test) score and/or %CDT. The main reasons for choosing these tools were as follows: a) several research papers have shown that the AUDIT is the most effective tool for identifying subjects with hazardous levels of drinking 23) , and b) although alcohol consumption continues to rise in most developed countries, those subject to hazardous drinking escape clinical diagnosis, so it is widely accepted that biochemical markers are useful for sensitive and effective detection of real alcohol consumption 24) , with %CDT being the only marker test approved by the FDA for the identification of hazardous drinking 25) . In our study, the proportion of workers that were screened as positive for one or both of the AUDIT and CDT tests was 13.8%.…”
Section: Discussionmentioning
confidence: 99%
“…liver transaminase levels and red blood cell mean cell volume) in combination with biochemical markers of nutritional status. Other newly developed biochemical markers for alcohol consumption [such as carbohydrate -defi cient transferrin (CDT), fatty acid ethyl esters (FAEEs), or ethyl glucuronide (EtG)] may be helpful (Borucki et al , 2005 ;Das et al , 2008 ;Delanghe and De Buyzere, 2009 ;Mancinelli and Ceccanti, 2009 ). Chronic alcohol consumption in the range of 50 -70 g/day induces hepatocytes to produce a transferrin molecule that is defi cient in carbohydrates.…”
Section: Effects Of Alcohol On Energy Metabolismmentioning
confidence: 99%